The importance of cervical cancer prevention: an integrative review (Research, Society and Development, 2021)
Objective: To carry out a review of the importance of preventing cervical cancer (CCU). Methods: This is an integrative literature review, whose inclusion criteria in the study were articles published from 2015 and data correlated to the object of study, the CCU, conceptualizing it, about its risk factors, treatment consequences, knowledge of women, among others related to the theme. Results: The application of organized tracking can reduce mortality from the disease by about 80% in more developed countries. In underdeveloped countries, results are lower due to limited access to health care. Even with forms of prevention, the number of women diagnosed at an advanced stage of the disease in the first assessment is around 70%, with women of lower socioeconomic status, indigenous, black, single, separated and widows having a greater chance of being diagnosed in advanced stages. Final considerations: The importance of prevention can be observed through the treatment of early and advanced stages, radiotherapy has more consequences than surgery, from stage IIB when parametrial invasion occurs, surgery becomes unfeasible, which leads to treatment more aggressive.